Robust control of pricing and inventory in a two-level supply network with competing retailers and delays in decision. (28th December 2021) - Zemzam, Azeddine; Alami, Jamila El; Alami, Nourddine El
In this paper, we construct a type of dynamic joint pricing and inventory supply model with switching time-varying delays and weights in pricing, scarcity effect in inventory and the uncertainties of parameters and customer's demand. This model is consisted of one distributor and two retailers under stock and price-dependent demand. Based on the rule of bounded rationality, the uncertain switched nonlinear system is approximated by the Takagi-Sugeno fuzzy model. Meanwhile, the fuzzy robust control method is introduced to minimise the bullwhip effect (BE), and a sufficient condition for the stability is presented utilising switched and delayed H-infinity state-feedback controller. The parallel distributed compensation is used to design the controller for the overall T-S fuzzy model. Finally, a simulation example is provided to investigate the influence of the different parameters as well as their relative uncertainties on the complex dynamic characteristics of the system and to illustrate the effectiveness of the proposed method. Moreover, the influence of the competition/partnership interactions on the dynamics and robustness is examined.